2010
DOI: 10.1167/iovs.09-5086
|View full text |Cite
|
Sign up to set email alerts
|

Pattern-Related Visual Stress, Chromaticity, and Accommodation

Abstract: Accommodative lag was greater in individuals susceptible to pattern-related visual stress and was reduced by a colored background.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…This means that the research investigating MISViS overlaps with other neurological conditions such as migraine and epilepsy (Huang et al 2003(Huang et al , 2011Wilkins et al 1984Wilkins et al , 2007Wilkins and NimmoSmith 1987) and is also referred to as visual stress, pattern related visual stress (Allen et al 2010), or visual discomfort (Conlon et al 1999(Conlon et al , 2009. The somatic symptoms of MISViS are heterogeneous, but can include asthenopia (i.e., general eye complaints) such as: pain in or around the eyes, eye fatigue, headaches, and photophobia (Evans et al 1996;Kriss and Evans 2005;Wilkins 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This means that the research investigating MISViS overlaps with other neurological conditions such as migraine and epilepsy (Huang et al 2003(Huang et al , 2011Wilkins et al 1984Wilkins et al , 2007Wilkins and NimmoSmith 1987) and is also referred to as visual stress, pattern related visual stress (Allen et al 2010), or visual discomfort (Conlon et al 1999(Conlon et al , 2009. The somatic symptoms of MISViS are heterogeneous, but can include asthenopia (i.e., general eye complaints) such as: pain in or around the eyes, eye fatigue, headaches, and photophobia (Evans et al 1996;Kriss and Evans 2005;Wilkins 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, despite the controversy about the role of colour in reading difficulty and its effect on dyslexia, the orthoptist should consider using coloured overlays or lenses when asthenopic symptoms persist and other clinical measures seem within normal limits. The clinician should also bear in mind that visual stress may in itself underlie increased accommodative lag 36 and persistent binocular vision weakness despite treatment. It remains the case, however, that many of those who have difficulty reading may have a range of conditions creating unpleasant symptoms when reading.…”
Section: Discussionmentioning
confidence: 99%
“…Others 35 have aso shown that accommodative lag increases more quickly in visually symptomatic readers, making blur more likely. This, however, has been linked to another visual disorder known as 'visual stress' by Allen et al, 36 who have shown that coloured backgrounds can reduce accommodative lag in visually symptomatic readers and that visual stress may cause accommodative fatigue and inaccuracy. Conversely, it is also possible that accommodative inaccuracy may make the perception of distortion more obvious since blur can enhance the appearance of spatial distortion.…”
Section: Accommodative Lag and Visual Discomfortmentioning
confidence: 99%
See 1 more Smart Citation
“…After 5 seconds, participants were read a list of 15 symptoms (shown in Table 1). The list of symptoms was that used by Allen et al 21 with the addition of 'fading'. Participants were asked to grade each symptom in order, on a scale from 0 to 10, where 0 meant they experienced no discomfort (no experience of the symptom) and 10 meant that the symptom was very uncomfortable.…”
mentioning
confidence: 99%